Quantitative data on the red deer (Cervus elaphus) population in the province of Forlì-Cesena - Luciano Cicognani; Franca Monti; Stefano Gellini; Filippo Baldassarri (Hystrix, the Italian Journal of Mammalogy, 2000)
Abstract The census of Red deer bucks during the rutting season was used in order to acquire quantitative data on the Red deer population inhabiting the northern part of the Foreste Casentinesi National Park. The census was conducted in September-October 1997 during the hours of highest rutting activity from a set of hearing points by recording the number and direction of ruts. The rutting range, extending over an area of about 11800 ha, was divided into two sectors covered by 31 and 30 hearing points respectively. A total of 77 bucks in sector 1 and 83 in sector 2 was recorded. From these figures we estimated a total population of 870 individuals and a density of 7.3 deers/kmq , comparable to the one recorded in the southern (Tuscan) part of the Park.